Structural and relaxation effects in proton wire energetics: model studies of the green fluorescent protein photocycle - Sun, Qiao; Wang, Sufan; Zhang, Hong; Li, Zhen; Pfisterer, Christoph; Fischer, Stefan; Nanbu, Shinko; Smith, Sean C. (Australian journal of chemistry, 2010)
We present the results of a systematic series of constrained minimum energy pathway calculations on ground state potential energy surfaces, for a cluster model of the proton chain transfer that mediates the photocycle of the green fluorescent protein, as well as for a model including the solvated protein environment. The calculations vary in terms of the types of modes that are assumed to be capable of relaxing in concert with the movement of the protons and the results demonstrate that the nature and extent of dynamical relaxation has a substantive impact on the activation energy for the proton transfer. We discuss the implications of this in terms of currently available dynamical models and chemical rate theories that might be brought to bear on the kinetics of this important example of proton chain transfer in a biological system.